Faktor-Faktor yang Mempengaruhi Agresivitas Pajak dengan Dimoderasi oleh Ukuran Perusahaan - Angelica Vidda Andariesta; Trisni Suryarini (Politeknik Ganesha Medan, 2023)
The highest tax revenue comes from income tax. The higher the taxable income of a company, it will affect the greater the cost of debt tax a company. It encourages companies to perform aggressive tax action. This study is conducted to test the audit committe independence, institutional ownership, corporate social responsibility, and leverage on tax aggressiveness moderated by firm size. The company's food and beverage subsector manufacturing listed in the Indonesian Stock Exchange for 2018-2021 and 32 served as a population for the study. The sample was taken using an purposive sampling technique which resulted in 63 units of analysis from 18 company's food and beverage subsector manufacturing. The data analyst technique used moderated regression analysis with IBM SPSS software version 25. The research result show that the corporate social responsibility has a negative effect on tax aggressiveness, while the audit committee independence, institutional ownership, and leverage do not affect on tax aggressiveness. Firm size has been proven to moderate the effect of corporate social responsibility on tax aggressiveness, but firm size can not moderate the effect of audit committee independence, institutional ownership, and leverage on tax aggressiveness. There are 7 companies that do not comply with OJK Regulation No. 55/PJOK.04/2015 concerning the formation and implementation guidelines of the audit committee so that the 7 companies are expecteded to be able to comply with the applicable regulations.